The comparative value of corn and sorghum grains as swine fattening feeds. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
In many parts of Kansas, sorghum grains are used extensively for hog feeding. In previous feeding tests with hogs at this station, ground kalir grain was shown to have about 90 percent of the value of corn. In a more recent test, ground Atlas sorgo grain was shower to have 93.5 percent of the value of corn. Since in recent years a number of new varieties of sorghum have been developed and grown throughout the state hog feeders have a desire to know about the feeding merits of these varieties, especially in times of high priced corn when it might be desirable to substitute sorghum grain for corn. They also wish to know whether the grain should be fed whole or ground.
Keywords: Swine; Corn; Sorghum grain; Gain